A Study Of Moisture Effects On The Breakdown Voltage And Spectral Characteristics Of Mineral And Palm Oil-Based Insulation Oils - Sharin , Ab Ghani (Asian Research Publishing Network (ARPN), 2016)
Based on a theoretical perspective,the primary function of insulation oils is to dissipate heat,and it serves as an insulator in between turn-to-turn windings in power transformers.To date,the majority of power transformer failures is attributed to the physicochemical reaction that takes place in the insulation oils due to the presence of heat,moisture content,oxidation and electrical stresses. Knowing that moisture content is one of the factors that leads to the degradation of transformer insulation oils,the main objective of this study is to examine the effects of moisture content on the breakdown voltage and Fourier transform infrared spectral characteristics of transformer insulation oils.Two types of insulation oils are chosen for this study:(1) conventional mineral-based insulation oil and (2)palm oil-based insulation oil which is a relatively new substitute for mineral-based insulation oils in Malaysia.The effects of moisture content is investigated by varying the amount of distilled water added into the oil samples from 1 to 5 ml, with an increment of 1 ml.Breakdown voltage test is conducted six times and the mean breakdown voltage is determined for each oil sample.The spectral characteristics of the oil samples are determined by means of Fourier transform infrared spectrometry.The breakdown voltage test and Fourier transform infrared spectrometry is carried out in accordance with the MS IEC 60156:2012 and ASTM D2144 standards,ensuring the reliability of the test procedures. Based on the findings of the study,it can be concluded that moisture content has a significant effect on the breakdown voltage and spectral characteristics of mineral and palm oil-based insulation oils – however,the effect is more pronounced for the mineral oil samples. Analysis of the Fourier transform infrared spectra reveals that the chemical composition of PFAE oil samples is not significantly influenced by moisture content and thus,this oil is a promising alternative for use as insulation oil in power transformers.